Climate Change and the Decline of Labor Share - Xincheng Qiu; Masahiro Yoshida (Institute of Labor Economics (IZA), 2024)
We study the impact of climate change on the labor share. Using a newly constructed dataset combining US county-level labor shares with climate variables, we find that extreme temperatures reduce labor share. This adverse effect is more pronounced in industries with higher outdoor exposure and automation potential. We also show that extreme temperatures accelerate the adoption of industrial robots. Overall, climate change accounts for 14% of the decline in labor share during 2001–2019. In the last century, however, the opposing effects of decreased cold days and increased hot days offset each other, consistent with the well-documented constancy of labor share.
Keywords: E25; Q54; O33; 330; climate change; labor share; automation